Does agricultural official development assistance facilitate foreign direct investment in agriculture: Evidence from 63 developing countries - Tian, Junyan (Wiley, 2023)
Although past studies have separately explored the direct impact of agriculture official development assistance (ODA) and foreign development investment (FDI) on agricultural production, the nexus between these two elements is often neglected. This article aims to understand the linkage between agricultural ODA and FDI, using data from 63 developing countries from 1991 to 2019. Poisson pseudo maximum likelihood estimations reveal that agricultural ODA considerably promotes FDI in the agriculture, fishery and forestry sectors (FDI_aff) by approximately 0.5%, while its impact on FDI in the food, beverages and tobacco industries (FDI_fbt) is overall insignificant. Geographical and ecological conditions play a decisive role in accounting for FDI in agriculture. While coastal and land‐rich countries receive a significantly higher amount of FDI_aff and FDI_fbt, tropical countries are evidently more attractive destinations for FDI_fbt. The empirical analysis also shows that a peaceful social environment encourages FDI_aff. Well‐established legal systems and reductions in corruption facilitate FDI_aff, whereas the impact of overall institutional quality on agricultural FDI is insignificant. Results suggest that donors prioritise agricultural initiatives with higher positive spillover effects, such as programmes supporting food crop production and agricultural research.